A Case Report Highlighting Uncommon Histopathological Finding of Papillary Thyroid Cancer within a Thyroglossal Duct Cyst - Zeb, Momina (Journal of Gandhara Medical and Dental Science, 2023)
This study discusses a case involving a 30-year-old male presented in ENT OPD with complaints of painless swelling in front of his neck. Papillary thyroid carcinoma originating from a thyroglossal duct cyst is an infrequent and atypical form of cancer. Typically, it remains undetected until surgical intervention and the optimal approach to its management is a subject of ongoing debate. Here, we present the case of a 30-year-old male who initially presented with a thyroglossal duct cyst but was subsequently diagnosed with papillary thyroid carcinoma. This case report focuses on suspecting having a Thyroglossal duct cyst, presented with painless swelling in front of the neck at the level of the hyoid bone. The mass moved when the tongue protruded but did not move when the patient swallowed. It exhibited a soft consistency during palpation, was not tender, movable, non-compressible, non-reducible, lacked fluctuation, and did not expand on the valsula while showing no changes in overlying skin temperature. TGD carcinoma can sometimes go undetected because it is a rare condition. When dealing with rapidly expanding neck masses in the midline, it’s essential to conduct appropriate examinations, including neck imaging and fine-needle aspiration cytology. While the Sistrunk procedure is adequate for squamous carcinoma, differentiated thyroid carcinoma typically necessitates total thyroidectomy as the recommended course of action.